Analyses of dual-phase lag heat conduction in 1-D cylindrical and spherical geometry – An application of the lattice Boltzmann method. (May 2016) - Mukherjee, Aritra; Lahiri, Arnab; Mishra, Subhash C.
Highlights: Dual-phase lag heat conduction was studied. Application of lattice Boltzmann method was extended. 1-D cylindrical and spherical geometry were considered. Comparisons were made with finite difference method results. Temporal temperature distributions for different lag ratios were analyzed. Abstract: Application of the lattice Boltzmann method to analyze dual-phase-lag heat conduction in a cylindrical and spherical geometry is reported. Thermal perturbation is caused by suddenly increasing the temperature of either or both inner and outer boundaries. Case of thermal perturbation with an adiabatic boundary is also considered. At different instants, radial temperature distributions are analyzed for a wide range of time lag ratios. To have an understanding how the dual-phase-lag heat conduction is different from the single-phase-lag one, in every case, temperature distribution are also presented for the single-phase-lag heat conduction. To check the accuracy of the lattice Boltzmann method results, the same problems are also solved using the finite difference method. Results of the two methods compare exceedingly well, and the lattice Boltzmann method has computational advantage over the finite difference method.